Uniqueness Perception and Willingness to Buy Protected Geographical Origin Versus Doppelgänger Brands - Neciunskas, Paulius; Tomaševičiūtė, Laura; Kazlauskė, Dovilė; Gineikienė, Justina; Kazlauskaitė, Rūta (Organizations and Markets in Emerging Economies, 2017)
This study explores what drives consumers’ judgments and decisions – uniqueness perception of a foreign product with protected geographical origin cue or uniqueness perception of a domestic doppelgänger product. We find that uniqueness perception of domestic brands has greater impact on willingness to buy domestic brands compared with the uniqueness perception of the brand holding geographical origin labels. Next, our data shows that uniqueness perception of domestic doppelgänger brands has influence not only on willingness to buy such brands (positive influence) but also negative influence on willingness to buy true and unique brands denominated by protected origin. Thus, by perceiving the uniqueness of a domestic brand positively, consumers discount the original, unique and legally protected brand and are less willing to buy such a brand. The study offers theoretical implications for ingroup positivity and outgroup negativity research as well as managerial implications for managers and policy makers indicating how to improve marketing efforts and regulatory support to geographical origin labels.
Keywords: uniqueness perception; protected geographical origin; doppelgänger product